Analysis of the Legal Consequences of Delays in Taking Over Shares Regarding KPPU Decision Number 05/KPPU-M/2022 - Ade Rizki Saputra; Siti Handayani Herdiyanti; Miliyandra; Ery Rachma Firsanti (Formosa Journal of Sustainable Research, 2024)
The KPPU's decision in the case of alleged delay in the acquisition of shares of PT Lestari Gemilang Intisawit in PT Nabati Agro Subur (number: 05/KPPU-M/2022) emphasizes the importance of notifying shareholders regarding the takeover of shares in accordance with Law Number 5 of 1999 concerning Monopoly Practices and Business Competition Against the Law. Good. After reviewing the decision, it was decided that PT Gemilang Lestari Intisawit had an obligation to notify the KPPU regarding the takeover as a subsidiary. However, even though this transaction increases the asset value and sales value of the parent company, there is a disparity between activities that are detrimental to other business actors and the fine imposed is only 1 billion rupiah. This shows the need for further evaluation of this decision to ensure fairness in law enforcement regarding fair business competition and protecting market interests